The Power of Asteroseismology for Early Stellar Evolution - Zwintz, Konstanze (Frontiers in Astronomy and Space Sciences, 2019)
Stars are the building blocks of planetary systems, clusters, associations, and galaxies. The evolution of stars is driven by physical processes in their interiors making theory of stellar interior structure and evolution an important ingredient of contemporary astrophysics. Despite its importance, this theory contains major shortcomings starting from the early stages of stellar evolution which significantly impact all subsequent evolutionary phases. Studying the pulsations of young intermediate-mass stars, i.e., conducting pre-main sequence (pre-MS) asteroseismology, has the potential to contribute to a better understanding of the processes acting during the earliest phases of stellar evolution. With ultra-precise observational data obtained from space and from ground in combination with improvements of our theoretical models for pre-MS stars, the field of pre-MS asteroseismology will advance in the future and provide important constraints for the input physics of early stellar evolution.